Can Inquiry-Based Learning Effectively Improve Vocational High School Students’ Critical Thinking and Conceptual Understanding? - Ghanifa Khoirul Khasanah; Nurhening Yuniarti; Irdayanti Binti Mat Nashir (Universitas Negeri Padang, 2026)
Modern industrial demands require vocational students to possess high-level analytical skills, making existing conceptual gaps in fundamental engineering laws a critical challenge. This study evaluates Inquiry-Based Learning in improving critical thinking and conceptual understanding of Ohms Law. While the Wilcoxon Signed-Rank Test measures within-group shifts, this quasi-experimental study utilizes a two-stage cluster random sampling technique and applies the Mann-Whitney test to compare cross-group gains among seventy-two participants. Data gathered via multiple-choice and analytical essay instruments revealed significant post-intervention gains favoring the inquiry class, further validated by a large experimental effect size value of minus zero point five rather than a solitary probability metric. Structured scientific inquiry effectively bridges abstract electrical theory with robust diagnostic competencies, prompting researchers to reconsider how statistical gain comparisons can definitively reshape traditional, lecture-based regimes in technical education